Steel beam–column joint with discontinuous vertical reinforcing bars - Hu, Ju-Yun; Hong, Won-Kee (Journal of Civil Engineering and Management, 2017)
The authors have previously proposed steel beam–column connections for precast concrete frames. The steel–concrete composite frames combined the advantages of the fast assembly of steel and the low cost of concrete structures. However, when not enough space is available at column–beam joints, steel sections from beams cannot be connected with column brackets. To address this issue, this paper explores the strategy of disconnecting some vertical reinforcing bars at the joints by connecting vertical steel reinforcements to steel plates placed above and below column steels, to provide a load transfer path. Loads from re-bars are transferred to steel plates, column steels, and back to steel plates and re-bars below the column steels. This strategy provided space for beam–column joints of composite frames. Extensive experiments were performed to verify load transfer from re-bars to steel plates above joints and from the steel plates to re-bars below the joint. The flexural load-bearing capacity of a column with a total of 24 vertical re-bars was compared to that of columns with discontinuous re-bars at the joints; the number of discontinuous re-bars at the joint used in the column specimens tested was 0 (0.0%), 4 (16.7%), 12 (50.0%), and 20 (83.3%).